(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to identify the theoretical concepts of the variables under study, which are represented by proactive leadership, organizational culture, and organizational commitment. It also aims to elucidate the impact of proactive leadership on both the variables of organizational culture and organizational commitment among employees within the Iraqi Al-Ahli Bank branch in Baghdad. The descriptive analytical method was used, and data was obtained through a questionnaire distributed to administrative staff at the Iraqi Al-Ahli Bank branch in Baghdad. The sample size was 36 individuals, with 35 valid questionnaires for analysis. The research results concluded that proactive leadership, with its components of proactive behavior and proactive personality, enhances organizational culture in the Iraqi Al-Ahli Bank, and that proactive leadership, with its components of proactive behavior and proactive personality, enhances organizational commitment in the Iraqi Al-Ahli Bank.